Remote workers' well-being: Are innovative organizations really concerned? A bibliometrics analysis - Joana Ribeiro; Filipa Pires da Silva; Pedro Rino Vieira (Journal of Innovation & Knowledge (JIK), 2024)
The coronavirus disease 2019 pandemic has accelerated the adoption of remote and hybrid forms of work in organizations. Despite the benefits that these flexible working models can bring to both employees and organizations, they are accompanied by a darker side. Heavy digital presence, increased workload, and blurred boundaries between work and life are some of the hindrances derived from remote working that directly affect employee well-being. Aware of the negative consequences that can lead to individual and organizational performance, companies are expected to define and adapt policies and regulations to protect employees and promote their well-being. However, literature addressing these research topics is scarce, and many contributions are dispersed across different fields. Therefore, we address this research gap by performing a bibliometric analysis of the contributions to remote employee well-being and complementing it with a content analysis. A sample of 64 publications was collected from two different databases. This study provides a performance measurement analysis of publications and citations and a scientific mapping of collaboration networks and emerging thematic trends. Furthermore, the content analysis allows us to understand how the organizational perspective on the well-being of employees in remote working settings has been addressed in the literature, clearly identifying opportunities for future research. Finally, the major challenges and research agendas are discussed.
Keywords: M14; 033; 650; Employee well-being; Digital well-being; Remote work; Organizational internal policies; Bibliometric analysis